2020
DOI: 10.3390/microorganisms8081162
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of the Gut Microbiota Composition in Moscow Long-Livers

Abstract: The aim was to assess the gut microbiota of long-livers from Moscow. This study included two groups of patients who signed their consent to participate. The group of long-livers (LL) included 20 participants aged 97–100 years (4 men and 16 women). The second group included 22 participants aged 60–76 years (6 men) without clinical manifestations of chronic diseases (healthy elderly). Gut microbiota was studied by 16S rRNA sequencing. Long-livers underwent a complex geriatric assessment as well as expanded blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Other Authors came to similar results when analyzing the microbiota of centenarians living in rural or isolated areas of China and Japan (Kong et al, 2016;Odamaki et al, 2016). Recently, studies involving centenarians from a rural area of India (Tuikhar et al, 2019) and Russia (Kashtanova et al, 2020) have been published, and the results were similar to those Italian, Chinese and Japanese populations in terms of increased biodiversity but with some peculiarities owing to the different lifestyle and nutritional habits.…”
Section: Gut Microbiota: At the Crossroad Among Inflammaging Immunose...supporting
confidence: 52%
“…Other Authors came to similar results when analyzing the microbiota of centenarians living in rural or isolated areas of China and Japan (Kong et al, 2016;Odamaki et al, 2016). Recently, studies involving centenarians from a rural area of India (Tuikhar et al, 2019) and Russia (Kashtanova et al, 2020) have been published, and the results were similar to those Italian, Chinese and Japanese populations in terms of increased biodiversity but with some peculiarities owing to the different lifestyle and nutritional habits.…”
Section: Gut Microbiota: At the Crossroad Among Inflammaging Immunose...supporting
confidence: 52%
“…While ageing studies in Italian, Irish and Thai individuals have reported a statistically significant reduction of Roseburia spp. abundance with age 28 , 38 , 40 , 95 , studies of Russian, Chinese and Korean populations have observed an increase 44 , 96 , 97 . In addition, contrary to many ageing-associated studies 2 , 46 , 95 , the pathobiont Bacteroides fragilis decreased with age in a general ageing-associated study in a healthy Indonesian cohort 98 .…”
Section: Gut Microbiome Changes With Ageingmentioning
confidence: 96%
“…The first category of studies provides a picture of how the gut microbiome changes with age in general, notwithstanding the fact that these are not longitudinal studies. Particularly noteworthy are studies of centenarians across various geographies and nationalities 36 44 . In general, the composition of the gut microbiome of centenarians (studied in countries/regions including Italy, Russia, China and India) is distinguished by a lower abundance of symbionts associated with health in younger age groups (such as Faecalibacterium spp.)…”
Section: Gut Microbiome Changes With Ageingmentioning
confidence: 99%
“…Christensenellaceae R-7 group is mainly involved in host amino acid and lipid metabolism ( Waters and Ley, 2019 ). Moreover, these bacteria were considered to be potentially beneficial since they are involved in the positive regulation of the intestinal environment and are associated with immune regulation and healthy homeostasis ( Kong et al, 2016 ; Kashtanova et al, 2020 ; Li et al, 2020 ). Dominant gut microbes are considered as the result of strong selection and long-term co-evolution with the host ( Groussin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%